Health Insurance and Public Health: Analyzing the Impact of Financing and Policy on Healthcare Access - Firmansyah (Yayasan Sinergi Kawula Muda, 2024)
Health insurance plays a crucial role in improving healthcare accessibility, particularly for vulnerable populations. This study systematically reviews the impact of health insurance on service utilization, affordability, and health outcomes across different countries. A comprehensive literature search was conducted using databases such as PubMed, Scopus, and Google Scholar, with predefined keywords and systematic inclusion criteria. The findings reveal that insurance coverage significantly enhances healthcare utilization and reduces financial barriers, yet disparities persist, particularly among low income and informal sector workers. Countries with mixed public private financing models tend to achieve better health equity and sustainability. Additionally, community based health insurance and digital innovations have shown promise in increasing participation and service efficiency. However, barriers such as policy fragmentation, limited infrastructure, and low public awareness hinder progress toward Universal Health Coverage. To address these challenges, policymakers must adopt inclusive financing strategies, strengthen public awareness campaigns, and invest in digital healthcare solutions. Future research should focus on evaluating the long term impact of these interventions to optimize health insurance models for broader accessibility and efficiency.